2009
DOI: 10.1109/jqe.2009.2013216
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Refractive Index and Micro-Raman Spectroscopy of Planar Waveguides in KGd(WO$_{4}$)$_{2}$ Formed by Swift Heavy Ion Irradiation

Abstract: Abstract-We report on the characterization of planar waveguides formed in the Raman-active crystal KGd(WO 4 ) 2 using swift carbon, fluorine, and oxygen ion irradiation. The characterization of the waveguiding regions was performed using high-resolution microreflectivity and micro-Raman spectroscopy. The high-resolution microreflectivity measurement fully characterizes the refractive index profile of the barrier formed by amorphization of the crystal and detects other index variations not detected by the m-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Electronic and nuclear energy losses as well as Au ion ranges were calculated using the SRIM code [10], and are presented in Figure 1.a) and b). KDy (WO4)2, as well as other tungstate crystals, is also a widely used material for the fabrication of integrated optical amplifiers and lasers [11][12][13]. Electronic and nuclear energy losses as well as N ion ranges were calculated using the SRIM code are shown in Figure 2.a) and b).…”
Section: Design and Fabrication Of The Waveguidesmentioning
confidence: 99%
“…Electronic and nuclear energy losses as well as Au ion ranges were calculated using the SRIM code [10], and are presented in Figure 1.a) and b). KDy (WO4)2, as well as other tungstate crystals, is also a widely used material for the fabrication of integrated optical amplifiers and lasers [11][12][13]. Electronic and nuclear energy losses as well as N ion ranges were calculated using the SRIM code are shown in Figure 2.a) and b).…”
Section: Design and Fabrication Of The Waveguidesmentioning
confidence: 99%
“…These layers had a low refractive index value of 1.87, in contrast to the three crystalline values which are above 2.0. Subsequently Merchant et al (Merchant et al, 2006b(Merchant et al, , 2009) characterized the obtained waveguides by optical techniques, finding that the Raman properties were preserved in the guiding region of the waveguide when irradiated with carbon ions but were considerably reduced when using oxygen and fluorine ions.…”
Section: Potassium Gadolinium Tungstate (Kgd(wo 4 ) 2 or Kgw)mentioning
confidence: 99%
“…In this study, swift-ion irradiation is proposed as an alternative method to fabricate thin, high-refractive index contrast, low-loss slab optical waveguides in bulk potassium double tungstate crystals. Preliminary studies on waveguide formation in KGd(WO 4 ) 2 by light [22] and heavy ion irradiation [23,24] have already demonstrated the potential of this technique. These studies have shown a higher refractive index change induced by swift heavy ion irradiation in KGd(WO 4 ) 2 (∼0.13 [23]) compared to light ion irradiation (He + : ∼0.01 [25], H + : ∼0.003 [22]), allowing for the fabrication of high-contrast waveguides in KRE(WO 4 ) 2 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on waveguide formation in KGd(WO 4 ) 2 by light [22] and heavy ion irradiation [23,24] have already demonstrated the potential of this technique. These studies have shown a higher refractive index change induced by swift heavy ion irradiation in KGd(WO 4 ) 2 (∼0.13 [23]) compared to light ion irradiation (He + : ∼0.01 [25], H + : ∼0.003 [22]), allowing for the fabrication of high-contrast waveguides in KRE(WO 4 ) 2 crystals. More recently, optical characterization has shown that low optical losses of <1.5 dB/cm at 1550 nm can be achieved in slab waveguides using carbon ion irradiation [26].…”
Section: Introductionmentioning
confidence: 99%